Effectiveness of Ferric Citrate in Controlling Hyperphosphatemia and Iron Deficiency in Chronic Kidney Disease (G 3-5) Patients: Compared with Calcium Acetate plus Ferrous Fumarate - Hasan, Sayful; Nazir, Nayana; Arjumand, Marina; Kamal, Rosanna Binte; Islam, Mohammad Qamrul; Umme Salma, Quazi Shaminah; Inshad, Tafhima Jannat; Sultana, Sadia; Huda, Md Nurul (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Ferric citrate is a novel oral, non-calcium containing phosphate binder, which has also been shown to replenish the iron deficient state of the Chronic Kidney Disease (CKD) patients. The purpose of this study was to compare the effectiveness of ferric citrate with calcium acetate plus ferrous fumarate in controlling hyperphosphatemia and iron deficiency in CKD (G 3-5) patients. Materials and methods: This open label randomized controlled trial was carried out in the Department of Nephrology, Chittagong Medical College Hospital. One hundred patients of CKD (G 3-5) were randomized to either ferric citrate or calcium acetate plus ferrous fumarate for a period of 12 weeks. Outcome measures were change in phosphate, corrected calcium, Parathohormone (PTH) hemoglobin, Transferrin Saturation (TSAT) ferritin, iron and Total Iron Binding Capacity (TIBC) after 12 weeks.Data were analyzed according to per protocol principle. Results: After 12 weeks of therapy, 36 from experimental group and 38 rom control group completed the study. There was a similar decrease in mean serum phosphate (1.2 mg/dl and 1.4 mg/dl respectively in experimental and control group, p=0.572). Improvement in mean hemoglobin was significantly higher in experimental group (1.3 gm/dl) compared to active control group (0.8 gm/dl) (p=0.023). Similarly, serum ferritin (Median 104 ng/ml versus 69.4 ng/ml, p=0.010) and transferrin saturation (Mean 9.8% versus 6.3%, p=0.002) were significantly increased in experimental group compared to control group. Serum iron was increased but TIBC was decreased in experimental group compared to control group (p<0.05). Serum corrected calcium was reduced in experimental group and increased in control group (p<0.001). In other hand, comparison of changes of serum PTH of both group at the end of the study was not significant (p=0.170). Conclusions: Ferric citrate was effective in controlling hyperphosphatemia and iron deficiency in CKD (G 3-5) patients. JCMCTA 2023 ; 34 (1) : 74-79